2018
DOI: 10.1038/s41598-018-31519-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of hysteresis due to a pseudo-photochromic effect in thermochromic smart window coatings

Abstract: The aim of thermochromic window coatings is to reduce the energy consumption in the built environment by passively switching between a high solar transmitting state at low temperatures and low solar transmitting state at high temperatures. Previous studies have highlighted the negative impact of phase transition hysteresis on the performance of reflection based thermochromic films. However in the literature, the best reported results have depended on vanadium dioxide nanoparticle composites and anti-reflective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…We mention in passing that the transmittance based metrics presented above are not the only parameters that smart window researchers need to consider when developing next generation coatings. Equally important, albeit broadly overlooked in the literature, are the hysteresis width and gradient of the coatings, which need to be tightly controlled or otherwise the performance of the windows may be inexorably compromised [187].…”
Section: Metrics For Thermochromic Window Performancementioning
confidence: 99%
“…We mention in passing that the transmittance based metrics presented above are not the only parameters that smart window researchers need to consider when developing next generation coatings. Equally important, albeit broadly overlooked in the literature, are the hysteresis width and gradient of the coatings, which need to be tightly controlled or otherwise the performance of the windows may be inexorably compromised [187].…”
Section: Metrics For Thermochromic Window Performancementioning
confidence: 99%
“…Several theoretical works [25,26,27] have highlighted the importance of reducing the hysteresis width of thermochromic films to improve their overall energy saving performance, as wide hysteresis loops mean that coatings are less responsive to changing climate conditions. Several previous works have shown that the hysteresis width can be reduced significantly by doping vanadium dioxide with metal ions [5,18], however this generally results in an increase in transition gradient [5] which has also been shown to be detrimental to the overall energy saving performance [25,28,27]. Table 1 shows a summary of literature for composite thermochromic coatings, from which we can see that improvements in solar modulation and visible transmission for composite coatings generally result in increased hysteresis width.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows a summary of literature for composite thermochromic coatings, from which we can see that improvements in solar modulation and visible transmission for composite coatings generally result in increased hysteresis width. It must also be noted how infrequently the transition gradient is discussed in the literature, despite having been shown to be critical to the overall energy saving performance [25,28,27]. In the only study found with a high optical performance (T lum = 48.5% & T sol = 15.7%) that reports both the transition hysteresis and gradient width, both hysteresis and gradient widths were found to be wide (17.4 & 11.3 • C respectively) [29].…”
Section: Introductionmentioning
confidence: 99%
“…The demand for energy-efficient smart windows utilizing thermochromic materials is constantly increasing due to their potential to dramatically reduce the energy consumption of the buildings by modulating the transmission of light and heat. [3][4][5][6][7] Vanadium dioxide (VO 2 ) has been widely investigated for smart windows because of its excellent thermochromic properties. [8][9][10] In particular, monoclinic M-phase VO 2 undergoes a metal-toinsulator transition (MIT) at a critical temperature of $68 C. [12][13][14] The monoclinic crystal structure of VO 2 displays infrared transparent below the critical temperature while in a rutile crystal structure it is infrared-reective above the critical temperature accompanied by abrupt changes in the electrical, magnetic, and optical properties.…”
Section: Introductionmentioning
confidence: 99%